Sesame oil and vitamin E co-administration may improve cardiometabolic risk factors in patients with metabolic syndrome: a randomized clinical trial - Farajbakhsh, Ali; Mazloomi, Seyed Mohammad; Mazidi, Mohsen; Rezaie, Peyman; Akbarzadeh, Marzieh; Ahmad, Saeedeh Poor; Ferns, G. A.; Ofori-Asenso, Richard; Babajafari, Siavash (European journal of clinical nutrition, 2019)
Objectives Metabolic syndrome (MetS) represents a clustering of metabolic abnormalities that are associated with an increased risk of type 2 diabetes and cardiovascular disease. We aimed to evaluate the effects of sesame oil enriched with vitamin E (vit E), sesame oil alone and sunflower oil on lipid profile, fasting blood glucose (FBG), malondialdehyde (MDA), high-sensitivity C-reactive protein (Hs-CRP), homeostatic model assessment (HOMA-IR), and blood pressure (BP) in patients with MetS. Subjects Overall, 75 individuals with MetS (aged 30–70 years) participated in this randomized, single-blind controlled trial. Patients were randomly allocated to: (1) Group A ( n = 25): sesame oil (30 ml/day) enriched with vit E (400 mg/day), (2) Group B ( n = 25): sesame oil (30 ml/day), (3) Group C ( n = 25): sunflower oil (30 ml/day). Anthropometric data, dietary intake, blood pressure, and biochemical markers, including fasting serum lipids, FBG, serum insulin, MDA, and hs-CRP were measured at baseline and at week 8. Results In individuals in the sesame oil enriched with vit E group (Group A), there were significant reductions in serum total cholesterol (TC), triglycerides (TG), FBG, HOMA-IR, MDA, hs-CRP, high-density lipoprotein (HDL-C) systolic and diastolic BP (for all the comparison p < 0.02). Similarly, in Group B (taking sesame oil alone), TC, TG, FBG, HOMA-IR, MDA, systolic and diastolic BP were significantly improved (for all the comparison p < 0.025), while there were no significant changes in serum HDL (baseline = 35.9 ± 7.2 mg/dL vs. 36.4 ± 6.2 mg/dL, p = 0.432) and hs-CRP (baseline = 4.38 ± 1.34 mg/dL vs. week 8 = 3.96 ± 1.7 mg/dL, p = 0.057) in second group. No significant changes in any of the studied clinical and anthropometric data were found in Group C (on sunflower oil). Conclusion Sesame oil (±vit E) was shown to beneficially affect several cardiometabolic indices (including lipids, FBG, BP, HOMA-IR, and MDA) in patients with MetS.